Adaptive feeding in the American oyster Crassostrea virginica: Complex impacts of pulsatile flow during pseudofecal ejection events. (2nd March 2020) - Wang, Linlin; Song, Junting; Bi, Hongsheng; Gray, Matthew; Fan, Chunlei; Liu, Ming; Mao, Xian‐Zhong
Abstract: Adaptive feeding is a strategy used by many organisms to maintain growth and reproduction success while encountering varying feeding conditions. Oysters are sessile benthic and non‐siphon filter feeders. Oysters are well adapted to modify the ambient microenvironment through their pumping behavior and particle selection activity. Rejection of unsuitable food particulates bound in pseudofeces via ejection events are an integral part of oyster feeding during which oysters produced strong flow opposite to their inhalant feeding flow. The strong opposite pulsatile flow during the ejection event inevitably disrupts the oyster's normal feeding cycle, but how oysters restart their feeding and allocate their energy consumption during an ejection event has not been investigated. The present study used particle image velocimetry (PIV) to examine the impact of ejection events on the feeding of the American oyster, Crassostrea virginica . The strong pulsatile flow resulting from pseudofecal ejection altered the external flow fields by moving water away from the shell. The initial feeding zone after pseudofecal ejection was relatively narrow, possessed a low pulsatile flow, and did not exploit the full flow field. The feeding zone gradually expanded as the pulsatile flow weakened. The strong shear rate at the stable feeding zone then sustained the feeding flow that facilitated oyster feeding. Furthermore, the volumetric fluxes often increased after the ejection event, suggesting increase in feeding efficiency after ejection events. These PIV studies provide new insight on the interactions between feeding oysters and the surrounding physical environment at small yet ecologically relevant scales.